Life-saving vascular access in vascular capital exhaustion: single center experience in intra-atrial catheters for hemodialysis - Pereira,Marta (2017)
Abstract Introduction: Intra-atrial catheter (IAC) placement through an open surgical approach has emerged as a life-saving technique in hemodialysis (HD) patients with vascular access exhaustion. Objective: To assess the complications of IAC placement, as well as patient and vascular access survival after this procedure. Methods: The authors retrospectively analyzed all seven patients with vascular capital exhaustion, without immediate alternative renal replacement therapy (RRT), who underwent IAC placement between January 2004 and December 2015 at a single center. Results: Seven patients were submitted to twelve IAC placements. Bleeding (6/7) and infections (3/7) were the main complications in the early postoperative period. Two (2/7, 29%) patients died from early complications and 5/7 were discharged with a properly functioning IAC. The most frequent late complication was catheter accidental dislodgement in all remaining five patients, followed by catheter thrombosis and catheter-related infections in the same proportion (2/5). During follow-up, two of five patients died from vascular accesses complications. After IAC failure, one patient was transferred to peritoneal dialysis and a kidney transplant was performed in the other. Only one patient remains on HD after the third IAC, with a survival of 50 months. The mean patient survival after IAC placement was 19 ± 25 (0-60) months and the mean IAC patency was 8 ± 11 (0-34) months. Conclusion: Placing an IAC to perform HD is associated to significant risks and high mortality. However, when alternative RRT are exhausted, or as a bridge to others modalities, this option should be considered.